Pemanfaatan Load Cell CZL601 untuk Pengukuran Derajat Layu Pada Pengolahan Teh Hitam - Sugriwan, Iwan; Muntini, Melania Suweni; Pramono, Yono Hadi (Lambung Mangkurat University Press, 2011)
This paper describes result of research about measurement of degree ofwilting in black tea processing. Degree of wilting was observed by measuring of tealeaves mass loss because the loss of water content. Mass sensor used is single pointload cell type CZL 601 that can measure up to 20 kg. Results of calibration of load cellgives the characteristic equation V = 0.0001 m + 0.2014 volts. Output of sensor isconnected with instrumentation amplifier which with applying three IC OP-07 whichsubsequently became data process for mirokontroller ATMega8. Data measurementresult interfaced on the LCD. Instrumentation system was implemented in miniprocess factory at Indonesian Research for Tea and Cinchona Gambung, Bandung.Results of measurement of mass loss in a trough of 48.39%, whereas in the samplebasket was 49.33%. Measuring the degree of wilting during the withering of theproduction process is 37.00%.